Children's Resilience in Facing the Loss of a Father Figure in an Islamic Boarding School in Yogyakarta - Siffa Eka Meiliani; Fitriah M. Suud (Alfuad: Jurnal Sosial Keagamaan, 2025)
Losing a father figure is a traumatic experience that can have a significant impact on children's psychological, emotional and social development. In Islamic boarding schools, the religious-communal environment has the potential to be an adaptive resource that strengthens children's resilience. This study aims to identify the protective factors that support their adaptation process and explore the resilience mechanisms of orphaned santri in dealing with losing a father figure. Using a phenomenological qualitative approach, data were obtained through in-depth interviews and participatory observation of six orphaned santri aged 15-18 years in a boarding school in Bantul, Yogyakarta. The analysis was conducted using the Interpretative Phenomenological Analysis (IPA) approach. The results showed that the resilience of santri was formed through seven main dimensions: emotion regulation, impulse control, optimism, causal analysis, empathy, self-efficacy, and the ability to reach out. The role of ustadz/ustadzah as a substitute father figure, social support from peers, and the Islamic values-based education system proved to be the main protective factors in building psychological resilience. These findings contribute to developing pesantren-based interventions to support orphans' emotional and social well-being. This study also recommends designing programs or training to improve the overall resilience of santri.